2001
DOI: 10.1271/bbb.65.1581
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change and Catalytic Activity of Horseradish Peroxidase in Oxidative Polymerization of Phenol

Abstract: The effects of solvent and reaction conditions on the catalytic activity of horseradish peroxidase (HRP) were investigated for oxidative polymerization of phenol in water/organic mixtures using hydrogen peroxide as an oxidant. Also, the structural changes of HRP were investigated by CD and absorption spectroscopy in these solvents. The results suggest that the yield of phenol polymer (the conversion of phenol to polymer) is strongly affected by the reaction conditions due to the structural changes of HRP, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…3. Similarly, the absorbance value of ϳ0.02, as reported by Akita et al, 30 is the nearly the same value obtained when absorbance measurement experiments were carried out for H 2 O 2 taken independently at a 635-nm wavelength. Therefore, it is evident that absorbance is maximum when specimens are taken in 1:1 volumetric ratio for the given molar concentrations of the specimen.…”
Section: Calculation Of Absorption Coefficientssupporting
confidence: 83%
See 1 more Smart Citation
“…3. Similarly, the absorbance value of ϳ0.02, as reported by Akita et al, 30 is the nearly the same value obtained when absorbance measurement experiments were carried out for H 2 O 2 taken independently at a 635-nm wavelength. Therefore, it is evident that absorbance is maximum when specimens are taken in 1:1 volumetric ratio for the given molar concentrations of the specimen.…”
Section: Calculation Of Absorption Coefficientssupporting
confidence: 83%
“…The results obtained from the absorbance measurements obtained from the experiments were compared with the previously published results. 28,30 In the published results, the concentration Fig. 3.…”
Section: Calculation Of Absorption Coefficientsmentioning
confidence: 98%
“…The Far-UV CD spectra of the conjugates revealed considerable decreases in the CD signals in the major bands at 215 nm and 225 nm and a shift of 225 nm band to 230 nm compared to the unmodified protein (Figure 4a). These CD changes were most pronounced for HRP-P(MeOx- b -BuOx) and are indicative of changes in the secondary structure of the HRP apo-protein (3031). At the same time there was little if any changes of CD signal in the Near-UV-vis spectra of the conjugates (Figure 4b) suggesting that the tertiary structure of HRP apo-protein and the microenvironment of the prosthetic heme remained unaffected by the conjugation (3031), even though the secondary structure of apo-protein was partially disrupted.…”
Section: Resultsmentioning
confidence: 99%
“…These CD changes were most pronounced for HRP-P(MeOx- b -BuOx) and are indicative of changes in the secondary structure of the HRP apo-protein (3031). At the same time there was little if any changes of CD signal in the Near-UV-vis spectra of the conjugates (Figure 4b) suggesting that the tertiary structure of HRP apo-protein and the microenvironment of the prosthetic heme remained unaffected by the conjugation (3031), even though the secondary structure of apo-protein was partially disrupted. The changes of the secondary structure may be ascribed to possible interactions between the block copolymer chain and α-helices on the surface of the apo-protein.…”
Section: Resultsmentioning
confidence: 99%
“…c) Structure of the film. Recently, through circular dichroic (CD) and adsorption spectroscopic analysis, Akita 33 and Schmidt 30 reported that both the secondary and the tertiary structure of the HRP change upon the reaction with H2O2. It is well known that HRP can be oxidized by H2O2 to HRP compound I, followed by the fast oxidation to HRP compound II, and possibly to compound III.…”
Section: Deflection Mechanismmentioning
confidence: 99%